Improvement of pozzolanic properties of oil palm boiler ash through heat treatment - Liew, Yu Xuan; Chin, Siew Choo; Goh, Hui Jun; Siti Asmahani, Saad; Gimbun, Jolius (EDP Sciences, 2023)
This paper presents the improvement of pozzolanic properties of oil palm boiler ash (OPBA) through heat treatment. The OPBA was obtained from oil palm mill in Pahang, Malaysia. The composition of OPBA was measured using X-ray fluorescence spectrometer which was used for its initial classification. It was found that freshly obtained OPBA had high carbon content (33.9%) and cannot be classified as pozzolan with only 15.73% of Al2O3, SiO2 and Fe2O3. Upon heating up to 600 °C for 2 h, the carbon content was eliminated and heated OPBA can be classified as pozzolan class F. When used as partial cement replacement, the 60-day compressive strength of OPBA-cement mixture peaked at 47.8 MPa for the pozzolan content of 15%. The compressive strength of OPBA-cement mixture decreases as the pozzolan content increases. © 2023 EDP Sciences. All rights reserved.